A Study on Interface Design to Provide Effective Meeting Summary Information: Focused on Narrative Chart and Topic Map Visualization - Lim, Soohyun; Park, Chanhee; Han, Hyunwoo; Ho, Jaejong; Hong, Junyup; Lee, Soojung; Lee, Kyungwon (Archives of Design Research, 2021)
Background There are many cases in which experts work collaboratively in the workplace. The proportion of workplace meetings continues to increase. The purpose of this study is to develop a visualization system that summarizes meetings, which occur in the workplace. Methods We confirmed that meetings can be classified into discussion-centered and topic-oriented types. These are proceeded with the review on studies of office meeting analysis. To devise a method of summarizing contents of meetings, we selected the visualization method. A narrative chart technique was selected for the summary visualization of the discussion-centered meeting, and a topic map technique was selected for the summary visualization of the topic-oriented meeting. Design tasks were selected according to their requirements through discussions with domain experts and a visualization expert. Results We conducted two controlled usability tests using actual meeting data. Narrative chart–based visualization was proven to effectively provide a general overview of the meeting and the participants’ utterance patterns. Topic map-based visualization demonstrated that the contents of the meeting can be inferred through the relationship between the information on various keywords. Conclusions This study proposed a meeting summary visualization system that is suitable for different workplace meeting types based on the requirements of meeting records and meeting type classification. Two visualization methods were developed to overcome the limitations of the previous one that provides all meeting summary information in one system without considering the differences in the characteristics of the meeting types.
Keywords: Data Visualization System; Design Research; Meeting Summarization; User Interface